2006
DOI: 10.1056/nejmoa060898
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin versus Unfractionated Heparin with Fibrinolysis for ST-Elevation Myocardial Infarction

Abstract: In patients receiving fibrinolysis for ST-elevation myocardial infarction, treatment with enoxaparin throughout the index hospitalization is superior to treatment with unfractionated heparin for 48 hours but is associated with an increase in major bleeding episodes. These findings should be interpreted in the context of net clinical benefit. (ClinicalTrials.gov number, NCT00077792.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
242
1
28

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(278 citation statements)
references
References 22 publications
7
242
1
28
Order By: Relevance
“…A meta-analysis of 9 clinical trials showed a 62% reduction in the frequency of symptomatic venous thromboembolism with extended use of heparins (mainly LMWHs) as compared with placebo after THA or TKA (37). Compared with unfractionated heparin, enoxaparin has been associated with a lower incidence of myocardial reinfarction in patients receiving fibrinolysis for ST-segment elevation acute MI (38). LMWHs reduce rates of recurrent ischemic stroke in patients with acute ischemic stroke, but subsequently increase the frequency of major bleeding (39).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 9 clinical trials showed a 62% reduction in the frequency of symptomatic venous thromboembolism with extended use of heparins (mainly LMWHs) as compared with placebo after THA or TKA (37). Compared with unfractionated heparin, enoxaparin has been associated with a lower incidence of myocardial reinfarction in patients receiving fibrinolysis for ST-segment elevation acute MI (38). LMWHs reduce rates of recurrent ischemic stroke in patients with acute ischemic stroke, but subsequently increase the frequency of major bleeding (39).…”
Section: Discussionmentioning
confidence: 99%
“…-Anticoagulantes: A enoxaparina deve ser administrada quando do diagnóstico do IAMCST nas seguintes doses: em pacientes com idade < 75 anos: 30 mg IV em bolo e após 1,0 mg/kg de peso subcutâneo de 12/12 horas até a alta hospitalar; em pacientes com idade ≥ 75 anos: não administrar o bolo e iniciar com 0,75 mg/kg subcutâneo de 12/12 horas 43 . Embora a enoxaparina não tenha demonstrado redução de mortalidade, houve redução do desfecho primário de morte ou infarto do miocárdio não fatal, sem um aumento importante de sangramento.…”
Section: -áCido Acetilsalicílico (Aas)unclassified
“…Após o estudo ASSENT-3 PLUS ter demonstrado resultados de segurança desfavoráveis, com doses de enoxaparina não ajustadas para o peso e em pacientes idosos (acima de 65 anos), foi planejado e executado o estudo ExTRACT TIMI 25 43 , com 20.506 pacientes com IAMCST tratados com fibrinolíticos, randomizados para enoxaparina durante o período de internamento ou heparina não fracionada por 48 horas. O regime de enoxaparina foi de 30 mg em bolus EV seguido por 1,0 mg/Kg SC a cada 12 horas (máximo de 100 mg para as duas primeiras doses).…”
Section: -Heparina Não Fracionada (Hnf)unclassified
See 1 more Smart Citation
“…Low molecular weight heparins are mostly used for the treatment of unstable angina and non-Q wave myocardial infarction, because of features such as: predictable anticoagulation, less bleeding, absence of laboratory monitoring and the dosage is based on body weight and can gradually be replaced by unfractionated heparin. 1 Low molecular weight heparin therapy is monitored by the anti-factor Xa assay. Low molecular weight heparins have a potency of greater than 70 units/ mg of anti-factor Xa activity and a ratio of anti-factor Xa to anti-thrombin activity of > 1.5.…”
Section: Letter To the Editormentioning
confidence: 99%